A Thematic Study of Ghazanfar’s Novels - Bibi, Sakeena; Zai, Altaf Yousaf; Hassan, Nadeem (sourcecoder, 2024)
Professor Gazanfar is well reputed scholar of Indian literature. His scholarly work published up to this time is consisted of nine Novels. Two short stories or Affsanas, three volume of poetry and three out lines. He has written a book on criticisms and literature and a drama or play. Ghazanfar made the cultural, socio-political inferiority Of women,oppression of workers,poor farmers and basic problems the subject of his Novels. He brought forth all the facts that can reflect the true reflection of the exploited Class.P resented the vices of the feudal system and their Luxuries ,which gives a picture Of the political and social environment of the period.In his Novels ,Ghazanfar has covered the problems of the subjugated sections of the society in a very subtle manner and examined all the factors due to which the society is reversing every type of decline due to the lack of attention.